(untitled) - Kassimali, Aslam (Victoria, Australia, 2005)
In this renowned text, Aslam Kassimali helps students develop an understanding of the basic principles of structural analysis. Emphasizing the intuitive, classical approach, the text covers the analysis of statically determinate and indeterminate beams, trusses, and rigid frames. It also presents an introduction to the matrix analysis of structures. Distinguished by the clarity and quality of its explanations, the text includes step-by-step procedures for analysis that build student problem solving skills. Enhancing students' understanding of the behavior of structures, the accompanying CD-ROM contains computer software for the analysis of plane frames, continuous beams, and trusses. The flexible format of the text and CD-ROM enables instructors to tailor the coverage to meet their course goals.
Keywords: Structural analysis ( engineering )